THE RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDE, AND PRENATAL VISITS IN PREGNANT WOMEN - Lilis Mamuroh; Sukmawati Sukmawati; Furkon Nurhakim (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2020)
According to the data of the Garut Health Office, the coverage of antenatal care visits has not yet reached the target in Garut district, especially in the Sukawening Public Health Center. Factors influencing the prenatal visits include knowledge and attitudes. The purpose of this study was to determine the relationship between knowledge, attitudes, and prenatal visits of pregnant women who have regular visits at Sukawening Public Health Center in Garut Regency. The research method used in this study was descriptive correlational using a cross-sectional approach. The samples were selected using the total sampling technique, 55 pregnant women involved in this study. The data were analyzed using the Chi-Square statistical test and correlation test. The results of the study showed that the knowledge of pregnant women was good (63.64%), they had a favorable attitude (60%), and the majority of them did antenatal care visits (7 4.55%). Statistical tests showed that there is a relationship between knowledge, attitudes, and prenatal visit with P-Value 0.017. as the antenatal visits in this study is still under the target, so there is a need to improve the pregnant women’s knowledge related to the importance of prenatal visit for the baby and mother during pregnancy.